ANALYSIS OF PROSPECTIVE BIOLOGY TEACHER CAPABILITIES IN ACQUIRING THE LEARNING CONCEPTS AND BIOLOGY SCIENCE MATERIALS IN JUNIOR HIGH SCHOOLS - Ningsih, Kurnia (Jurnal Pendidikan Matematika dan IPA, 2020)
This study was aimed to analyse the ability of prospective Biology teachers to master the learning concepts and Biology Science materials in Junior High Schools. The used method in this study was a descriptive analysis, involving some prospective teachers (the students who were taking micro-teaching courses (PPL-1) in even semester of 2017/2018 academic year) in the Biology Education Study Programme FKIP Untan, as the research subjects. A total of 30 university students with GPA ≥ 3.00 were randomly selected. The instrument in this study was an ability assessment of learning concepts and materials of Biology Science in junior high schools. The data analysis was done in descriptively qualitative and quantitative methods; including data collection, data reduction, data presentation, data analysis using means and percentages, and conclusions eventually. The results showed that the prospective Biology teachers in mastering the concept of learning obtained an average value of 76.89 with A, B, and C grades respectively, 46.67%, 40.00%, and 13.33%. For mastering the biology science concept, it was obtained an average value of 75.73 with grade A, B, and C respectively, 33.33%, 46.67%, and 20.00%. It was certainly concluded that the ability of prospective biology teachers in mastering the concepts of learning and the materials of Biology Science was classified into the good category.